Babymouse. [13], Cupcake tycoon - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2010)
The school library is hosting a fundraiser and Babymouse is determined to win the grand prize--and help the school--but to win she will have to outsell her classmates, including her nemesis, Felicia Furrypaws.
3.1
3-6.
3-6
Keywords: Animals -- Comic books, strips, etc -- Juvenile fiction; Babymouse (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Fund raising -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Animals -- Fiction; Babymouse (Fictitious character) -- Fiction; Cartoons and comics; Fund raising -- Fiction; Mice -- Fiction; Animals -- Comic books, strips, etc -- Fiction; Babymouse (Fictional character) -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Fund raising -- Comic books, strips, etc -- Fiction; Graphic novels; Mice -- Comic books, strips, etc -- Fiction; Graphic novels